Studi Perhitungan Biaya Pada Kegiatan Pengupasan Overburden Pada PIT 5 PT. Indochin Resources Jobsite PT. Energi Cahaya Industritama: Cost Calculation Study On Overburden Removal Activities At Pit 5 Pt. Indochin Resources Jobsite Pt. Industritama Light Energy - Hikmawati; Henny Magdalena; Windhu Nugroho; Harjuni Hasan; Lucia Litha Respati (Jurnal Pengetahuan dan Pendidikan, 2023)
During the stripping and hauling of overburden, there are several things that affect this activity, namely the productivity of the equipment, working front conditions, loading methods, and working hours. Before carrying out mining activities, it is necessary to calculate a budget, the aim is to provide an overview of the costs to be incurred by the company for mining activities. The results of research that has been carried out for one month shows that the productivity of the tools used for stripping overburden is obtained as follows. The productivity of the Sany SY365H PRO excavator in fleet 1 was 221.13 bcm/hour and the productivity of the Sany SY365H PRO excavator in fleet 2 was 226.11 bcm/hour. And the productivity of the DT SYZ322C-8S conveyance in Fleet 1 is 37.37 bcm/hour and the productivity of the DT SYZ322C-8S conveyance in Fleet 2 is 37.38 bcm/hour. The costs that must be incurred for the tools used in overburden stripping activities are obtained as follows. The ownership cost of the Sany SY365H PRO Excavator digging-loading equipment is US$ 9.93/hour, operating costs are US$ 32.55/hour. The cost of owning the DT SYZ322C-8S means of transportation is US$ 0.54/hour, and operating costs are US$ 12.14/hour.